The Institutional Ownership and Disclosure of Sustainability Report with Environmental Uncertainty as Moderation Variables - Delfy, Delfy; Bimo, Irenius Dwinanto (Universitas Negeri Semarang, 2021)
This study aims to analyze institutional ownership's direct effect as a corporate governance mechanism on sustainability reporting. This study also considers external factors, environmental uncertainty as moderating variables. Sustainability reporting is measured using the Global Reporting Initiative standard, which consists of standards, economic (GRI 200), environmental (GRI 300), and social (GRI 400). The sample selection uses purposive sampling. This study's sample is a non-financial company listed on the Indonesia Stock Exchange (IDX) and publishes successive sustainability reports from 2017 to 2019. Hypothesis testing uses panel data regression (Balanced Panel) with a random effect model, using STATA 14.2 statistical software. In a direct relationship, the study results provide empirical evidence that institutional ownership has a positive effect on sustainability reporting. The higher the percentage of share ownership by the institution, the better the sustainability reporting. Meanwhile, environmental uncertainty does not moderate institutional ownership of sustainability reporting when considering external factors as moderating variables.